Answer:
7)(3,-1)
8. (3,-1/4)
9. (1/3,1)
10.(2,-1)
Explanation:
7) 2x + 2y = 4
2x – 2y = 8
------------------------
4x = 12
Divide by 4
4x/4 = 12/4
x =3
Now we need to find y
2x+2y =4
2(3) + 2y =4
6+2y =4
Subtract 6 from each side
6-6 +2y = 4-6
2y = -2
Divide by 2
2y/2 = -2/2
y= -1
(3,-1)
8. 2x + 4y = 5
3x – 4y = 10
-------------------
5x = 15
Divide by 5
5x/5 = 15/5
x=3
Now we need to find y
2x+4y = 5
2(3) +4y = 5
6+4y =5
Subtract 6 from each side
6-6+4y = 5-6
4y = -1
Divide by 4
4y/4 = -1/4
y = -1/4
(3,-1/4)
9. 3x + 4y = 5
6x – 3y = -1
Multiply the first equation by -2
-2(3x + 4y) = 5*-2
-6x-8y = -10
Now add this equation to the 2nd equation to eliminate x
-6x-8y = -10
6x – 3y = -1
----------------------
-11y = -11
Divide by -11
-11y/-11 = -11/-11
y=1
Now we need to find x
3x+4y =5
3x+4(1) =5
3x+4=5
Subtract 4 from each side
3x+4-4 =5-4
3x = 1
Divide by 3
3x/3 = 1/3
(1/3,1)
10. 2x - 2y = 5
4x + 6y = 5
Multiply the first equation by 3 to eliminate y
3( 2x - 2y) = 5 *3
6x -6y = 15
Now add this to the second equation
6x -6y = 15
4x + 6y = 5
-----------------
10x = 20
Divide by 10
10x/10 = 20/10
x=2
Now we need to find y
4x+6y=5
4(2) +6y = 5
8+6y = 5
Subtract 8 from each side
8-8+6y=5-8
6y = -3
Divide by 6
6y/6 = -3/6
y=-1/2
(2,-1/2)